Bio-inspired design and realization of a novel multimode amphibious robot - Weibing Wang; Junzhi Yu; Rui Ding; Min Tan (2009 IEEE International Conference on Automation and Logistics, 2009)
This paper deals with an improved design scheme for an amphibious robot inspired by various amphibian principles in animal kingdom. Considering the propulsive features of existing amphibian modes synthetically, a novel hybrid propulsive mechanism that integrates fish-like swimming with wheel-paddle-fin movements is proposed. The robot is able to implement speedy and efficient fish-like or dolphin-like swimming and to perform flexible wheel-like terrestrial movements, which can switch between these two patterns by a specialized swivelling device. Critical engineering realization issues involving morphological optimization, buoyancy calculation and waterproof sealing are discussed. In particular, the design philosophy of modularity has been incorporated into the development of the robotic prototype. Preliminary testing partially validates the feasibility of multimode gaits both on land and in water.